Comparing phase‐ and amplitude‐gated volumetric modulated arc therapy for stereotactic body radiation therapy using 3D printed lung phantom. Issue 2 (22nd January 2019) - Lee, Minsik; Yoon, KyoungJun; Cho, Byungchul; Kim, Su Ssan; Song, Si Yeol; Choi, Eun Kyung; Ahn, SeungDo; Lee, Sang‐Wook; Kwak, JungWon
Abstract: Purpose: To compare the dosimetric impact and treatment delivery efficacy of phase‐gated volumetric modulated arc therapy (VMAT) vs amplitude‐gated VMAT for stereotactic body radiation therapy (SBRT) for lung cancer by using realistic three‐dimensional‐printed phantoms. Methods: Four patient‐specific moving lung phantoms that closely simulate the heterogeneity of lung tissue and breathing patterns were fabricated with four planning computed tomography (CT) images for lung SBRT cases. The phantoms were designed to be bisected for the measurement of two‐dimensional dose distributions by using EBT3 dosimetry film. The dosimetric accuracy of treatment under respiratory motion was analyzed with the gamma index (2%/1 mm) between the plan dose and film dose measured under phase‐ and amplitude‐gated VMAT. For the validation of the direct usage of the real‐time position management (RPM) data for respiratory motion, the relationship between the RPM signal and the diaphragm position was measured by four‐dimensional CT. By using data recorded during the beam delivery of both phase‐ and amplitude‐gated VMAT, the total time intervals were compared for each treatment mode. Results: Film dosimetry showed a 5.2 ± 4.2% difference of gamma passing rate (2%/1 mm) on average between the phase‐ vs amplitude‐gated VMAT [77.7% (72.7%–85.9%) for the phase mode and 82.9% (81.4%–86.2%) for the amplitude mode]. For delivery efficiency, frequent interruptions were observed during the phase‐gated VMAT, which stopped the beam delivery and required a certain amount of time before resuming the beam. This abnormality in phase‐gated VMAT caused a prolonged treatment delivery time of 366 s compared with 183 s for amplitude‐gated VMAT. Conclusions: Considering the dosimetric accuracy and delivery efficacy between the gating methods, amplitude mode is superior to phase mode for gated VMAT treatment.